Geopolitical Tensions Around the Horn of Africa - Kun, Tamás (Honvédségi Szemle – Hungarian Defence Review, 2025)
The Red Sea crisis has significantly altered cargo routes in maritime transport, resulting in a ten percent increase in shipping costs and several days longer transportation times. Around the Horn of Africa, several attacks occurred that were carried out by Houthi rebels from Yemen. The Iran-backed group uses these attacks as a form of message to the United States and its allies, showing sympathy for Gaza in the Israel-Hamas War. The neighbouring Djibouti had to reinforce its coast guard patrols to ensure security and respond to the rising tensions in the area. The paper examines the situation in the Gulf of Aden and the Red Sea, analysing the possible reasons behind the strikes against vessels and other targets in the region, where all members of the “Four Policemen” were present in the arrangement of the conflict.